Exploring Pronunciation Errors Produced by Indonesian Hospital Administration Students in Ordering Hospital Supplies - Ulinuha, Atik; Hidayati, Yeni Nurmala; Susilowati, Palupi (English Teaching Journal : A Journal of English Literature, Language and Education, 2024)
For hospital administration, clear and accurate communication is essential, especially when ordering hospital supplies. Pronunciation errors committed by hospital administration students can cause misunderstandings that have far-reaching harmful effects. By examining students’ pronunciation errors, the qualitative study was presented in this study. Data were collected from video conversations in ordering medical supplies in hospital settings, analyzed for errors, and written in the phonetic transcription. According to the findings, respondents made errors in substitution (87%), omission (10%), and insertion (3%). Meanwhile, 47% of the errors were caused by discrepancies in the sound systems between L1 and L2, 37% by mother tongue interference, and 16% by inconsistent vowel usage. This study should be helpful to the hospital administration students to make them aware of the significance of proper pronunciation.